Test pole piece, lithium battery and preparation method

By using a test electrode sheet composed of a base film and electrode layer in the battery, the problems of short service life, high cost and poor stability of the existing reference electrode are solved, and the accurate measurement of the positive and negative potential of the battery and the normal transmission of lithium ion are achieved, thereby improving the stability and safety of the battery.

CN115411218BActive Publication Date: 2025-03-07BYD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110578210.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-26
Publication Date
2025-03-07
Estimated Expiration
2041-05-26

AI Technical Summary

Technical Problem

The existing reference electrodes have problems in the battery field with low service life, high cost, poor stability and blocking lithium ion transmission, which affects the normal charging and discharging performance of the battery.

Method used

A test electrode sheet is adopted, which includes a base film and an electrode layer, and the resistivity of the base film is greater than 6Ω·m2·m-1. The electrode layer is composed of a voltage stabilizer, a conductive agent and a binder. The test electrode sheet is prepared by preparing the electrode layer slurry and applying it to the base film.

Benefits of technology

Accurate measurement of the positive and negative electrode potential of the battery is achieved, which improves the stability and safety of battery use, while allowing lithium ions to be transmitted, avoiding the risk of lithium excretion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115411218B_ABST
    Figure CN115411218B_ABST
Patent Text Reader

Abstract

The present invention provides a test electrode, a lithium battery and a preparation method thereof, comprising: a base film, the surface resistivity of the base film being greater than 6Ω·m 2 ·m ‑1 , electrode layer, the electrode layer is located on one side of the base film, the electrode layer includes a voltage stabilizer, a conductive agent and a binder, the mass of the voltage stabilizer: the mass of the conductive agent: the mass of the binder = a:b:c, where a is 15-25, b is 0.3-0.6, and c is 0.3-0.6. Therefore, the positive and negative potentials of the battery can be accurately measured by setting the test electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a test pole piece and a lithium battery and a preparation method thereof. Background Art

[0002] For batteries, the potentials of the positive and negative electrodes can be measured with the help of reference electrodes to determine their relative values, especially the potential of the negative electrode to lithium, which can help determine whether lithium deposition occurs in the battery, so as to avoid safety accidents such as sudden capacity drop or even lithium dendrites piercing the diaphragm and short circuit. In actual production, the quality of the positive and negative plates of the battery during the charging and discharging process can be measured by setting the reference electrode, thereby providing a reliable basis for improving product quality. At the same time, the reasons for the reduction of battery capacity and failure can also be analyzed in time through measurement. Therefore, the reference electrode is of great significance in the field of batteries. However, the mainstream reference electrodes currently used have certain problems during use, such as disturbance of current and obstruction of ion transmission. Summary of the invention

[0003] This application is based on the inventor's discovery of the following problems:

[0004] The inventors have discovered that in the field of storage batteries, the mainstream reference electrodes currently used include copper wire-plated lithium electrodes and aluminum wire-coated lithium iron phosphate electrodes. However, the above two reference electrodes have certain problems in different aspects. Among them, the copper wire-plated lithium electrode has a low service life and cannot meet the needs of long-term use; due to the limitations of the existing manufacturing process, the aluminum wire-coated lithium iron phosphate electrode needs to coat lithium iron phosphate on a thicker aluminum wire, which increases the cost and has poor stability in use. In addition, the above two commonly used reference electrodes will block the lithium ion deintercalation reaction between the positive and negative electrodes to varying degrees, and cannot play the role of a reference electrode well.

[0005] The present application aims to solve one of the technical problems in the related art to a certain extent.

[0006] In one aspect of the present application, the present invention provides a test electrode, comprising: a base film, wherein the resistivity of the base film is greater than 6Ω·m 2 ·m -1 , an electrode layer, the electrode layer is located on one side of the base film, the electrode layer includes a voltage stabilizer, a conductive agent and a binder, the mass of the voltage stabilizer: the mass of the conductive agent: the mass of the binder = a:b:c, wherein a is 15-25, b is 0.3-0.6, and c is 0.3-0.6. Thus, the positive and negative potentials of the battery can be accurately measured by setting the test electrode.

[0007] In another aspect of the present invention, the present invention provides a method for preparing the above-mentioned test electrode.

[0008] Provide a base film, prepare an electrode layer slurry, the slurry includes a voltage stabilizer, a conductive agent and a binder, the solid content of the electrode layer slurry is 5-20%, and the electrode layer slurry is coated on the base film to obtain the test electrode, wherein the mass fraction of the voltage stabilizer in the electrode layer slurry is 92-98%; the conductive agent in the electrode layer slurry is carbon nanotubes, and the mass fraction of the carbon nanotubes is 1.2-3.9%; the mass fraction of the binder in the electrode layer slurry is 1.2-3.9%. The test electrode described above can be prepared by this method, and thus, the method for preparing the test electrode has all the characteristics and advantages of the test electrode described above, which will not be repeated here. In summary, a test electrode capable of accurately measuring the positive and negative potentials of a battery can be prepared by a relatively simple method.

[0009] In another aspect of the present invention, the present invention proposes a lithium battery, comprising: a negative electrode sheet, an insulating diaphragm, the insulating diaphragm is located on one side of the negative electrode sheet, a positive electrode sheet, the positive electrode sheet is located on the side of the insulating diaphragm away from the negative electrode sheet, and at least one test electrode sheet, the test electrode sheet is located between the positive electrode sheet and the negative electrode sheet, wherein the electrode layer of the test electrode sheet is located on the side close to the insulating diaphragm, and the test electrode sheet is the test electrode sheet described above. Therefore, the lithium battery has all the characteristics and advantages of the test electrode sheet described above, which will not be repeated here. In summary, the potential of the positive and negative electrodes of the lithium battery can be obtained more accurately by setting the test electrode sheet, and the test electrode sheet uses the diaphragm as the carrier of the electrode layer, so that the test electrode sheet monitors the positive and negative electrodes to the lithium potential while allowing the transmission of lithium ions between the positive and negative electrodes, which will not affect the normal charge and discharge performance of the target battery, and will also prevent the risk of lithium plating caused by the previous test electrode sheet not allowing lithium ions to pass; so the test electrode sheet in the present invention can accurately test the potential of the positive and negative electrodes, and will not affect the various performances of the target battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0011] Figure 1 It shows a schematic structural diagram of a test pole piece according to an embodiment of the present invention;

[0012] Figure 2 It shows a schematic structural diagram of a test pole piece according to another embodiment of the present invention;

[0013] Figure 3 A schematic diagram of the structure of a lithium battery according to an embodiment of the present invention is shown;

[0014] Figure 4A schematic structural diagram of a lithium battery according to another embodiment of the present invention is shown;

[0015] Figure 5 A schematic structural diagram of a lithium battery according to another embodiment of the present invention is shown;

[0016] Figure 6 A scanning electron microscope image showing the test pole piece of Example 1;

[0017] Figure 7 Another scanning electron microscope image of the test electrode piece of Example 1 is shown;

[0018] Figure 8 A charge-discharge cycle test diagram of the test electrode of Example 1 is shown;

[0019] Fig. 9 Another charge-discharge cycle test diagram of the test electrode of Example 1 is shown;

[0020] Fig.10 Another charge-discharge cycle test diagram of the test electrode of Example 1 is shown;

[0021] Fig.11 The equilibrium potential test diagram of the test electrode of Example 1 is shown.

[0022] Explanation of reference numerals: 10: base film; 20: electrode layer; 30: adhesive layer; 100: negative electrode sheet; 200: positive electrode sheet; 300: insulating separator. DETAILED DESCRIPTION

[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0024] In one aspect of the present application, the present invention provides a test electrode, referring to Figure 1 , comprising: a base film 10, the resistivity of the base film being greater than 6Ω·m 2 ·m -1, the electrode layer 20, the electrode layer 20 is located on one side of the base film 10, the electrode layer 20 includes a voltage stabilizer, a conductive agent and a binder, the mass of the voltage stabilizer: the mass of the conductive agent: the mass of the binder = a:b:c, wherein a is 15-25, b is 0.3-0.6, and c is 0.3-0.6. The base film provides a supporting structure and insulation for the electrode layer. The voltage stabilizer in the electrode layer can keep the electrode layer on the test electrode at a stable potential. The conductive agent is an indispensable component in the electrode layer slurry, which can improve the ionic conductivity and electronic conductivity of the electrode layer, so that the polarization of the electrode layer is reduced as much as possible when adjusting the charge state. The addition of the binder can make the conductive network of the electrode layer completely connected, avoiding cracks or even material falling on the electrode layer, causing instability of the electrode layer. The adverse effect of the test electrode on the reaction between the positive and negative electrodes is reduced, so that by setting the above-mentioned test electrode between the positive and negative electrodes of the battery, a more accurate positive and negative electrode potential, especially the negative electrode's potential to lithium, can be obtained, which can help determine whether lithium deposition occurs in the battery, so as to avoid safety accidents such as sudden capacity drop or even lithium dendrites piercing the diaphragm to cause a short circuit.

[0025] For ease of understanding, the following is a brief description of the principle by which the test electrode can achieve the above beneficial effects:

[0026] The inventors have found that in the field of storage batteries, common reference electrodes include copper wire lithium-plated electrodes and aluminum wire coated lithium iron phosphate electrodes. Among them, the copper wire lithium-plated electrode has a relatively low service life, requires frequent lithium plating, and has poor long-term stability; the aluminum wire coated lithium iron phosphate electrode is limited by the manufacturing process in the prior art, and lithium iron phosphate needs to be coated on a thicker aluminum wire, but the thicker aluminum wire is easy to disturb the current around it, and at the same time it will damage the positive and negative electrodes. In addition, the above two commonly used reference electrodes will block the reaction between the positive and negative electrodes, causing the positive and negative electrode potentials measured by the reference electrode to deviate, making the potential measurement results inaccurate, and therefore cannot play the role of a reference electrode well. In the present application, the inventor proposes a test electrode which can be used as a reference electrode for potential detection between the positive and negative electrodes of a battery. The test electrode will not hinder the ion transmission between the positive and negative electrodes of the battery, nor will it hinder the reaction between the positive and negative electrodes, greatly improving the accuracy of the positive and negative electrode potential test results of the battery. Moreover, since the area size of the test electrode proposed in the present invention can be selected according to actual conditions and it also has good flexibility, the test electrode proposed in the present invention can be distributed in various areas of the battery, greatly improving the accuracy of the positive and negative electrode potential test results, thereby realizing the function of detecting the respective potentials of the positive and negative electrodes during the use of the battery, and then by detecting the real-time potential of the battery during use, early warning is provided for abnormal conditions such as lithium deposition and sudden drop in battery capacity, thereby improving the stability and safety of the battery.

[0027] According to some embodiments of the present invention, the voltage stabilizer has a charge and discharge platform during constant current charging or constant voltage charging, and the voltage stabilizer is charged to its charge and discharge platform to stabilize the potential of the test electrode, so that the test electrode acts as a reference electrode. The type of voltage stabilizer is not particularly limited, for example, the voltage stabilizer may include at least one of lithium iron phosphate and lithium titanate, wherein the voltage of lithium iron phosphate when charged to its voltage stability is 3.41V, and the voltage of lithium titanate when charged to its voltage stability is 1.55V.

[0028] According to some embodiments of the present invention, the median particle size of the voltage stabilizer in the electrode layer slurry is not particularly limited. For example, the median particle size of the voltage stabilizer in the electrode layer slurry can range from 0.8 to 1.1 microns. When the median particle size of the voltage stabilizer is less than 0.8 microns, the median particle size of the voltage stabilizer is too small. Due to the presence of pores on the base membrane, the voltage stabilizer particles will pass through the pores on the base membrane, causing the structural stability of the electrode layer to deteriorate, or enter the pores of the base membrane, blocking the pores of the base membrane, causing a short circuit, and causing the base membrane to fail. When the median particle size of the voltage stabilizer is greater than 1.1 microns, the particle size of the voltage stabilizer is too large, which increases the thickness of the electrode layer and makes the surface uneven, and the potential stabilization effect cannot be achieved well.

[0029] According to some embodiments of the present invention, the base membrane should have a certain pore size and porosity to allow ions from the positive and negative electrode reactions of the battery to pass through, while preventing electrons from passing through due to its own high resistivity. In addition, it should have good chemical and electrochemical stability to prevent the base membrane from being corroded by the electrolyte. The type of base membrane is not particularly limited. For example, the base membrane may include at least one of polypropylene and polyethylene.

[0030] According to some embodiments of the present invention, reference Figure 2 , an adhesive layer 30 may be further included between the base film 10 and the electrode layer 20, and the adhesive layer is located on one side of the base film. Furthermore, the electrode layer may be located on the side of the adhesive layer away from the base film. The provision of the adhesive layer may further improve the flatness of the electrode layer, improve the adhesion strength of the electrode layer on the base film, and have little effect on the migration of lithium ions in the battery. Taking the case where the test electrode is located between the positive electrode and the insulating diaphragm as an example, when the electrode layer of the test electrode is located on the side facing the insulating diaphragm, the adhesive layer on the test electrode may improve the insulation between the electrode layer and the positive electrode in the battery.

[0031] According to some embodiments of the present invention, the type of material forming the bonding layer is not particularly limited. For example, the bonding layer may include at least one of polyvinylidene fluoride and polymethyl methacrylate.

[0032] According to some embodiments of the present invention, the thickness of the electrode layer on the test electrode piece is related to the potential stability of the test electrode piece and the positive and negative electrode reactions of the battery. The thickness of the electrode layer on the test electrode piece is not particularly limited. For example, the thickness of the electrode layer of the test electrode piece can range from 5 to 10 microns. When the thickness of the electrode layer of the test electrode piece is less than 5 microns, the electrode layer thickness is too thin, the potential stability after charging is poor, and it cannot serve as a reference electrode. When the thickness of the electrode layer of the test electrode piece is greater than 10 microns, the electrode layer thickness is too thick, which affects the normal reaction between the positive and negative electrodes of the battery.

[0033] According to some embodiments of the present invention, the surface density of the voltage stabilizer in the electrode layer on the base film is not particularly limited. For example, the surface density of the voltage stabilizer in the electrode layer on the base film may be in the range of 0.05-0.1 g / dm 2 When the surface density of the voltage stabilizer in the electrode layer on the base film is less than 0.05 g / dm 2 When the voltage stabilizer content per unit area of ​​the test electrode is too small, it cannot stabilize the potential of the test electrode; when the surface density of the voltage stabilizer in the electrode layer on the base film is greater than 0.1g / dm 2 When the voltage stabilizer content per unit area of ​​the test electrode is too high, the air permeability of the diaphragm is reduced, and the impedance is increased, which affects the normal reaction between the positive and negative electrodes of the battery.

[0034] According to some embodiments of the present invention, the type of the conductive agent in the electrode layer is not particularly limited. For example, the conductive agent in the electrode layer may be carbon nanotubes, which are used to form a network structure to connect and conduct the scattered voltage stabilizers in the electrode layer. The diameter and aspect ratio of the carbon nanotubes in the electrode layer are not particularly limited. For example, the diameter of the carbon nanotubes in the electrode layer may be 10-50nm, and the aspect ratio of the carbon nanotubes may be 50-100. When the diameter and aspect ratio of the carbon nanotubes are within the above range, the carbon nanotubes have the advantages of a smaller diameter, a longer tube length, and good conductivity. Using the carbon nanotubes as a conductive agent can provide a certain support for the coating of the voltage stabilizer on the base film, which can reduce the polarization of the test electrode as a reference electrode and improve the air permeability of the test electrode.

[0035] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned test electrode, comprising:

[0036] S100: Provide base film

[0037] According to some embodiments of the present invention, a base film is provided in this step, and the type of the base film is consistent with the above description, which will not be repeated here. Specifically, the base film may include at least one of polypropylene and polyethylene.

[0038] S200: preparing electrode layer slurry,

[0039] According to some embodiments of the present invention, the electrode layer slurry is prepared in this step, and the composition of the electrode layer slurry is not particularly limited. For example, the electrode layer slurry may include a voltage stabilizer, a conductive agent, and a binder, wherein the solid content of the electrode layer slurry is in the range of 20-30%. The dry part of the solid content of the electrode layer slurry is mainly composed of the voltage stabilizer, that is, the addition amount of the voltage stabilizer in the electrode layer slurry needs to be controlled within an appropriate range, so that the electrode layer can not only play a role in stabilizing the voltage, but also minimize the adverse effects on the reaction between the positive and negative electrodes of the battery.

[0040] According to some embodiments of the present invention, the mass fraction of the voltage stabilizer in the electrode layer slurry is not particularly limited, for example, the mass fraction of the voltage stabilizer in the electrode layer slurry can range from 92% to 98%. When the mass fraction of the voltage stabilizer in the electrode layer slurry is less than 92%, the content of the voltage stabilizer in the electrode layer is too small to stabilize the potential of the test electrode; when the mass fraction of the voltage stabilizer in the electrode layer slurry is greater than 98%, the content of the voltage stabilizer in the electrode layer is too large, the permeability of the diaphragm is reduced, the impedance is increased, the lithium ion conduction is hindered, and the normal reaction between the positive and negative electrodes of the battery is affected.

[0041] According to some embodiments of the present invention, the type of the conductive agent in the electrode layer slurry is not particularly limited, for example, the conductive agent can be carbon nanotubes, and the mass fraction of the carbon nanotubes in the electrode layer slurry is not particularly limited, for example, the mass fraction of the carbon nanotubes in the electrode layer slurry can range from 1.2 to 3.9%. When the mass fraction of the carbon nanotubes in the electrode layer slurry is less than 1.2%, the content of the carbon nanotubes in the electrode layer is too small to form a network structure, and thus the voltage stabilizer cannot be connected, and the electrode layer cannot play a role in stabilizing the potential; when the mass fraction of the carbon nanotubes in the electrode layer slurry is greater than 3.9%, the content of the carbon nanotubes in the electrode layer is too high, the dispersion effect is poor, the carbon nanotubes will be entangled together, and the conductive network formed is incomplete.

[0042] According to some embodiments of the present invention, the mass fraction of the binder in the electrode layer slurry is not particularly limited, for example, the mass fraction of the binder in the electrode layer slurry is in the range of 1.2-3.9%. When the mass fraction of the binder in the electrode layer slurry is controlled within the above range, it helps to improve the peeling force of the electrode layer slurry on the base film and prevent the electrode layer slurry from falling off.

[0043] According to some embodiments of the present invention, the type of the binder is not particularly limited, for example, the binder may be polyvinylidene fluoride.

[0044] According to some embodiments of the present invention, in order to improve the dispersibility of the voltage stabilizer and the carbon nanotubes in the electrode layer, the electrode layer slurry may further include: a dispersant. Specifically, the dispersant may include N-methylpyrrolidone.

[0045] According to some embodiments of the present invention, the specific method for preparing the electrode layer slurry is not particularly limited. Specifically, the method for preparing the electrode layer slurry may include: adding a binder and a dispersant to a mixing device to obtain a binder slurry, adding carbon nanotubes to a mixing device to obtain a conductive slurry, adding a voltage stabilizer to a mixing device to obtain a coarse electrode layer slurry, and sieving the coarse electrode layer slurry to obtain an electrode layer slurry. Thus, an electrode layer slurry having a voltage stabilizer with an appropriate particle size range can be obtained.

[0046] S300: coating the electrode layer slurry on the base film to obtain a test electrode.

[0047] According to some embodiments of the present invention, since the surface energy of the base film is relatively small, it is difficult to directly apply the electrode layer slurry; therefore, an adhesive layer can be applied on one side of the base film before applying the electrode layer slurry on the base film, and the electrode layer slurry can be applied on the side of the adhesive layer away from the base film. In this way, the adhesive layer and the binder in the electrode layer slurry can work together to ensure that the electrode layer slurry is evenly applied on the base film without falling off. At the same time, the adhesive layer can prevent the electrode layer material from short-circuiting with the positive electrode sheet or negative electrode sheet material in the battery, thereby improving the insulation.

[0048] According to some embodiments of the present invention, after obtaining the test electrode piece, the method may further include: electrically connecting the wire to the test electrode piece by using a hot pressing method, thereby facilitating subsequent battery assembly.

[0049] In another aspect of the present invention, the present invention provides a lithium battery, referring to Figure 3 , Figure 4 and Figure 5 , including: a negative electrode sheet 100, an insulating diaphragm 300, the insulating diaphragm 300 is located on one side of the negative electrode sheet 100, a positive electrode sheet 200, the positive electrode sheet 200 is located on the side of the insulating diaphragm 300 away from the negative electrode sheet 100, and at least one test electrode sheet, the test electrode sheet is located between the positive electrode sheet 200 and the negative electrode sheet 100, wherein the electrode layer 20 of the test electrode sheet is located on the side close to the insulating diaphragm 300, and the test electrode sheet is the aforementioned one. The test electrode sheet can be one or more, and those skilled in the art can choose according to actual conditions. Therefore, the lithium battery has all the characteristics and advantages of the aforementioned test electrode sheet, which will not be repeated here. In summary, through the setting of the test electrode sheet, the positive and negative electrode potentials of the battery can be measured more accurately, the operating status and stability of the electrodes can be accurately known, and the safety of the lithium battery can be improved.

[0050] According to some embodiments of the present invention, the position of the test electrode in the lithium battery is not particularly limited, as long as the test electrode is located between the positive electrode and the negative electrode. Figure 3 The test electrode sheet may be located between the negative electrode sheet 100 and the insulating separator 300, referring to Figure 4 The test electrode can be located between the positive electrode 200 and the insulating diaphragm 300, referring to Figure 5 The test electrode can be located between the negative electrode 100 and the insulating membrane 300, and the electrode layer 20 of the test electrode can contact the insulating membrane 300. Similarly, the test electrode can be located between the positive electrode and the insulating membrane, and the electrode layer of the test electrode can contact the insulating membrane.

[0051] According to one embodiment of the present invention, when the test electrode is located between the positive electrode and the insulating membrane, that is, the electrode layer in the test electrode is separated from the negative electrode by the insulating membrane, the base film of the test electrode can contact the positive electrode.

[0052] It should be pointed out that the electrode layer on the test electrode needs to be charged to 50% state of charge (SOC) with the negative electrode assembly before being used as the reference electrode in the three electrodes to meet subsequent use requirements. When the test electrode is located between the positive electrode and the insulating diaphragm, the test electrode and the negative electrode of the lithium battery can be charged; when the test electrode is located between the negative electrode and the insulating diaphragm, the test electrode and the negative electrode of the lithium battery are also charged. Technical personnel in this field can make a choice based on actual conditions.

[0053] According to some embodiments of the present invention, when the base film of the test electrode is made of a flexible polymer material, the test electrode also has a certain flexibility, that is, it is a flexible test electrode. When the test electrode is a flexible test electrode, during battery assembly, the test electrode can be bent to match a battery with a wound battery cell inside.

[0054] It should be pointed out that the shape of the test electrode is not particularly limited, and those skilled in the art can select it according to the shape of the battery and the position where the voltage needs to be detected. For example, the shape of the test electrode can be a long sheet, a fan, an arc, etc.

[0055] According to some embodiments of the present invention, the method for charging the test electrode is not particularly limited. For example, the test electrode can be charged by a constant current charging method or a constant voltage charging method to make its voltage be at a charging and discharging platform.

[0056] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0057] In the examples described below, unless otherwise specified, the reagents used can be purchased from the market or prepared by the methods described in the present invention.

[0058] Embodiment 1:

[0059] 1. Provide base film,

[0060] 2. Prepare electrode layer slurry. The composition of the electrode layer slurry is as follows: the voltage stabilizer is lithium iron phosphate with a median particle size of D50 = 0.9 microns, the conductive agent is carbon nanotubes with a tube diameter of 30 nm and an aspect ratio of 70, polyvinylidene fluoride is used as a binder, and N-methylpyrrolidone is used as a dispersant. The mass fraction of the voltage stabilizer is 93.2%, the mass fraction of the carbon nanotubes is 3.1%, and the mass fraction of the binder is 3.7%.

[0061] Add a binder and a dispersant into a mixer and stir for 1 hour to obtain a binder slurry, add carbon nanotubes into the mixer and stir for 30 minutes to obtain a conductive slurry, add a voltage stabilizer into the mixer and stir for 1.5 hours to obtain a coarse electrode layer slurry, and sieve the coarse electrode layer slurry to obtain an electrode layer slurry.

[0062] 3. Select polyvinylidene fluoride as the adhesive layer, apply the bonding layer on one side of the base film, and apply the electrode layer slurry on the side of the adhesive layer away from the base film to obtain a test electrode.

[0063] The results show that the solid content of the electrode layer slurry of the test electrode in Example 1 is 9%, the mass of the voltage stabilizer in the test electrode: the mass of the conductive agent: the mass of the binder = 15:0.5:0.6, the thickness of the electrode layer of the test electrode is 8 microns, and the surface density of the voltage stabilizer in the electrode layer of the test electrode on the base film is 0.06g / dm 2 .

[0064] The scanning electron microscope image corresponding to the test electrode in Example 1 is as follows: Figure 6 and Figure 7 As shown, it can be seen that the surface flatness of the electrode layer is relatively high, the carbon nanotubes connect the lithium iron phosphate particles to form a network structure on the surface of the base membrane, and the pores on the surface of the base membrane are not blocked by the lithium iron phosphate particles.

[0065] Comparative Example 1:

[0066] Prepare aluminum wire coated lithium iron phosphate electrode, the steps are as follows:

[0067] 1. Provide an aluminum wire with a diameter of about 200 microns, and remove the enameled wire on one end of the aluminum wire, with a removal length of about 10 mm;

[0068] 2. Prepare electrode layer slurry. The composition of the electrode layer slurry is as follows: the voltage stabilizer is lithium iron phosphate with a median particle size of D50 = 0.9 microns, the conductive agent is carbon nanotubes with a tube diameter of 30 nm and an aspect ratio of 70, polyvinylidene fluoride is used as a binder, and N-methylpyrrolidone is used as a dispersant. The mass fraction of the voltage stabilizer is 93.2%, the mass fraction of the carbon nanotubes is 3.1%, and the mass fraction of the binder is 3.7%.

[0069] Add a binder and a dispersant into a mixer and stir for 1 hour to obtain a binder slurry, add carbon nanotubes into the mixer and stir for 30 minutes to obtain a conductive slurry, add a voltage stabilizer into the mixer and stir for 1.5 hours to obtain a coarse electrode layer slurry, and sieve the coarse electrode layer slurry to obtain an electrode layer slurry.

[0070] 3. Remove the aluminum wire from one end of the enameled wire and insert it into the electrode layer slurry. Take it out and bake it at 100°C until dry.

[0071] The test electrode in the above-mentioned embodiment 1 and the aluminum wire coated lithium iron phosphate electrode in the comparative example 1 are respectively assembled to the corresponding positions inside the lithium battery where the voltage needs to be tested.

[0072] For Example 1, the electrical testing steps are as follows:

[0073] 1. Provide negative electrode sheet.

[0074] 2. Provide an insulating separator so that the insulating separator is located on one side of the negative electrode sheet.

[0075] 3. Provide a positive electrode sheet so that the positive electrode sheet is located on the side of the insulating membrane away from the negative electrode sheet.

[0076] 4. Provide at least one test electrode, and place the test electrode between the positive electrode and the insulating diaphragm, wherein the electrode layer of the test electrode is located on the side close to the insulating diaphragm.

[0077] 5. The test electrode in step 4 is charged with a constant current to the charging platform of lithium iron phosphate (approximately 50% SOC state).

[0078] 6. Charge and discharge the positive and negative electrodes at 0.02C, and test the potential between the positive and negative electrodes during the charge and discharge process to test the lithium deintercalation platform of the negative electrode.

[0079] 7. Charge and discharge the positive and negative electrodes at 0.33C. After 50 charge and discharge cycle tests, detect the stability of the potential between the positive and negative electrodes during the cycle.

[0080] 8. Assemble the test electrode and lithium sheet into a button battery, charge the button battery at 0.01C, relax for 2h every time the SOC is charged to 10%, and test the equilibrium potential of the test electrode to lithium.

[0081] For Comparative Example 1, the electrical test steps are as follows:

[0082] 1. Provide negative electrode sheet.

[0083] 2. Provide an insulating separator so that the insulating separator is located on one side of the negative electrode sheet.

[0084] 3. Provide a positive electrode sheet so that the positive electrode sheet is located on the side of the insulating membrane away from the negative electrode sheet.

[0085] 4. Provide at least one aluminum wire coated lithium iron phosphate electrode, and place the aluminum wire coated lithium iron phosphate electrode between the positive electrode sheet and the insulating separator.

[0086] 5. The aluminum wire coated lithium iron phosphate electrode in step 4 is charged with a constant current to a charging platform of the lithium iron phosphate (approximately 50% SOC state).

[0087] 6. Perform 0.02C charge and discharge on the positive and negative electrodes, and test the potential between the positive and negative electrodes and the test electrode during the charge and discharge process, and test the lithium deintercalation platform of the negative electrode;

[0088] 7. Charge and discharge the positive and negative electrodes at 0.33C. After 50 charge and discharge cycle tests, detect the stability of the potential between the positive and negative electrodes during the cycle.

[0089] The test results are as follows:

[0090] The charge and discharge cycle test results of the test electrode in Example 1 are as follows: Figure 8 As shown, the reference Figure 8 , it can be seen that the lithium iron phosphate battery is used in Example 1, that is, lithium iron phosphate is used as the positive electrode, graphite is used as the negative electrode, and lithium iron phosphate is coated on the diaphragm as the test electrode piece, that is, three electrodes are used to test the positive and negative electrode potentials; after the lithium iron phosphate battery is cycled 50 times at 1 / 3C, the potentials of the positive and negative parameters still maintain good electrochemical stability, that is, the lithium iron phosphate coated on the diaphragm as the test electrode piece can ensure the normal lithium ion deintercalation in the target battery, and can also ensure the stability of the positive and negative electrode potentials of the test; reference Fig. 9 When a ternary battery is used, that is, nickel-cobalt-manganese as the positive electrode, graphite as the negative electrode, and lithium iron phosphate coated on the diaphragm as the test electrode, that is, three electrodes are used to test the positive and negative electrode potentials; after the nickel-cobalt-manganese battery is cycled 50 times at 1 / 3C, the potentials of the positive and negative electrodes still maintain good electrochemical stability. Fig.10, a ternary battery is used, that is, nickel-cobalt-manganese as the positive electrode, graphite as the negative electrode, and lithium iron phosphate coated on the diaphragm as the test electrode, that is, three electrodes are used to test the positive and negative electrode potentials; when the nickel-cobalt-manganese battery is cycled at a low current of 0.02C, the three-order lithium insertion platform of the negative electrode can be well tested. This shows that the test electrode also has good electrochemical stability under low current.

[0091] The results show that the negative electrode to lithium potential test results of the lithium battery equipped with the test electrode in Example 1 are more accurate than the negative electrode to lithium potential test results of the lithium battery equipped with the aluminum wire coated lithium iron phosphate electrode in Comparative Example 1. Since the aluminum wire used for coating the lithium iron phosphate electrode is relatively thick (about 200 microns, if it is too thin, the operation process will be difficult), and the thickness of the lithium iron phosphate slurry coated on the aluminum wire is uneven, the lithium iron phosphate material is easy to fall off, resulting in inaccurate potential detected by the test electrode; at the same time, since the aluminum wire is relatively thick, the shape of the positive and negative electrodes will be deformed, and the presence of the aluminum wire will block the lithium insertion and extraction reaction between the positive and negative electrodes, causing the lithium ion concentration around the aluminum wire to increase, and there is a risk of lithium precipitation on the negative electrode, which is also the reason for the inaccurate potential detected by the test electrode; and when the test electrode in Example 1 of the present application is used as the reference electrode for the negative electrode to lithium potential test, the reference electrode is used as the reference electrode. Fig.11 Since the test electrode in Example 1 completely allows lithium ions to pass through, it does not affect the lithium insertion and extraction reaction between the positive and negative electrodes, and no lithium precipitation reaction occurs around the test electrode, so the lithium potential is always stable, that is, the potential measurement result of the negative electrode is more accurate. At the same time, the thickness of the test electrode in Example 1 is very thin (about 20 microns), which has little effect on the diffusion path of lithium ions between the positive and negative electrodes. This is also the reason why the test electrode in Example 1 is more accurate in detecting the potential. For the negative electrode to lithium potential, when the test electrode in this application is used as a reference electrode for testing, the deviation of the test result of the negative electrode to lithium potential is reduced by more than 10mV compared with the conventional aluminum wire coated lithium iron phosphate electrode as the reference electrode for testing.

[0092] In the description of this specification, the description with reference to the terms "one embodiment", "another embodiment", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples without contradiction.

[0093] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A test electrode, characterized in that: Used for potential detection between the positive and negative electrodes of a battery. During detection, the test electrode is located between the positive electrode and the negative electrode. The test electrode includes: Base film, the surface resistivity of the base film is greater than 6Ω·m 2 ·m -1 , an electrode layer, wherein the electrode layer is located on one side of the base film, The electrode layer includes a voltage stabilizer, a conductive agent and a binder. The voltage stabilizer has a charge and discharge platform during constant current charging or constant voltage charging. By charging the voltage stabilizer to the charge and discharge platform, the test electrode piece acts as a reference electrode. The mass of the voltage stabilizer: the mass of the conductive agent: the mass of the binder = a:b:c, Among them, a is 15-25, b is 0.3-0.6, and c is 0.3-0.

6.

2. The test electrode according to claim 1, characterized in that: The voltage stabilizer includes at least one of lithium iron phosphate and lithium titanate, and the median particle size of the voltage stabilizer is 0.8-1.1 microns.

3. The test electrode according to claim 1, characterized in that: The base film includes at least one of polypropylene and polyethylene.

4. The test electrode according to claim 3, characterized in that: Further including: The adhesive layer is located on one side of the base film, and the electrode layer is located on a side of the adhesive layer away from the base film.

5. The test electrode according to claim 4, characterized in that: The bonding layer includes at least one of polyvinylidene fluoride and polymethyl methacrylate.

6. The test electrode according to claim 1, characterized in that: The thickness of the electrode layer is 5-10 microns.

7. The test electrode according to claim 1, characterized in that: The voltage stabilizer in the electrode layer has a surface density of 0.05-0.1 g / dm 2 .

8. The test electrode according to claim 1, characterized in that: The conductive agent in the electrode layer is a carbon nanotube, the diameter of the carbon nanotube is 10-50 nanometers, and the aspect ratio of the carbon nanotube is 50-100.

9. A method for preparing the test electrode according to any one of claims 1 to 8, characterized in that: include: Providing a base film, Prepare electrode layer slurry, the slurry includes voltage stabilizer, conductive agent and binder, the solid content of the electrode layer slurry is 5-20%, Applying the electrode layer slurry on the base film to obtain the test electrode sheet, Wherein, the mass fraction of the voltage stabilizer in the electrode layer slurry is 92-98%; The conductive agent in the electrode layer slurry is carbon nanotubes, and the mass fraction of the carbon nanotubes in the electrode layer slurry is 1.2-3.9%; The mass fraction of the binder in the electrode layer slurry is 1.2-3.9%.

10. The method according to claim 9, characterized in that After obtaining the test electrode, the method further includes: electrically connecting the wire to the test electrode by using a hot pressing method.

11. A lithium battery, characterized in that: include: Negative electrode, an insulating diaphragm, the insulating diaphragm being located on one side of the negative electrode sheet, A positive electrode sheet, the positive electrode sheet is located on a side of the insulating diaphragm away from the negative electrode sheet, At least one test electrode, the test electrode is located between the positive electrode and the negative electrode, wherein the electrode layer of the test electrode is located on a side close to the insulating diaphragm, and the test electrode is the test electrode according to any one of claims 1 to 8.

12. The lithium battery according to claim 11, characterized in that: The test electrode is located between the positive electrode and the insulating diaphragm.

Citation Information

Patent Citations

  • Integrated flexible electrode

    CN104916809A